Газоносність вугільних пластів та фізико-механічнині властивості порід покрівлі і підошви поля шахти № 1 ”Тяглівська” Львівсько-Волинського басейну - Бучинська, І.В.; Явний, П.М.; Яринич, О.О.; Шевчук, О.М. (Геотехническая механика, 2012)
Сопоставлены данные по изучению газоносности угольных пластов поля шахты № 1
―Тягловская‖ и физико-механическим свойствам пород их непосредственной кровли и подошвы. Благоприятными яляются условия для выработки пластов b4, n8
в, n8. Несколько сложнее – для пластов n9, n7 в, n7 1, что вызвано низкой стойкостью пород кровли. Наиболее сложной прогнозируется ситуация для эксплуатации пласта n7 из-за низной стойкости и способности его кровли к обрушениям. Угольные пласты (кроме b4) находятся в метановой зоне. Их газоносность значительна, содержание метана в газовой смеси высокое. Это будет составлять дополнительные трудности при эксплуатации. Data on studies of the gas-bearing potential of coal seams of the Tyagliv-1 mine field are
correlated as well as physical-mechanical properties of their immediate base and roof. Favorable conditions are known to exist for working of the seams b4, n8 в, n8. Somewhat more composite ones are observed for the seams n9, n7в, n7 1 that was caused by low stability of the roof rocks. The most composite situation is forecasted for exploitation of the seam n7 one to low stability and ability of its roof for landslides. Coal seams (exsepting b4) lie in the methane zone. Their gas-bearing potential is suffcient, methane content in a gas mixture is high. That will cause additional difficalties in the process of exploitation.